Mitigasi Lingkungan Sekolah Dan Masyarakat Terhadap Keselamatan Bermain Anak - Kuswanto, Cahniyo Wijaya; Efaliana, Yudesta; Dona Dinda Pratiwi (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
Accidents involving young children, both at home and at school, continue to increase. One of the causes is the lack of safe play facilities and the overprotective attitude of parents. This study aims to examine the relationship between teachers' and parents' knowledge of injury risks and the preventive actions they take to protect children during physical activities. The research method uses a quantitative approach with a correlational method, involving observation, structured interviews, and questionnaires. Data were analyzed using validity tests, reliability tests, and classical assumption tests through SPSS. The results of the study show a positive correlation between teachers' and parents' knowledge and the implementation of preventive measures, such as close supervision, the use of protective equipment, and preparedness in dealing with emergencies. Basic knowledge of first aid and cooperation between teachers, parents, and medical staff proves to create a safer environment. In conclusion, good knowledge of injury risks enables teachers and parents to be more proactive in preventing injuries, thereby creating a safe play environment that supports children's optimal development.